2021
DOI: 10.3122/jabfm.2021.01.200351
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Patient EXperience (APEX) in COPD Registry: Study Design and Strengths

Abstract: The Advancing the Patient Experience (APEX) in Chronic Obstructive Pulmonary Disease (COPD) registry (https:// www.apexcopd.org/) is the first primary care health system-based COPD registry in the United States. While its ultimate goal is to improve the care of patients diagnosed with COPD, the registry is also designed to describe real-life experiences of people with COPD, track key outcomes longitudinally, and assess the effectiveness of interventions. It will retrospectively and prospectively collect inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This has been facilitated by the development of standardized data collection methods, use of harmonized definitions to monitor co-morbidity, symptom, and exacerbation burdens, as well as care and treatment of patients with COPD, using both EHR and PRIO data sources. 18,19 The preponderance of smokers or ex-smokers, overweight or obese patients, and high prevalence of comorbidities in our study, and the almost equal distribution of males and females have been reported by others. [24][25][26][27][28] Our prevalence of nonsmokers (12% in both COPD-RD and APEX-COPD) is in agreement with that reported by Celli and colleagues (13%), 29 but lower than that estimated by the Centers for Disease Control and Prevention (25%).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This has been facilitated by the development of standardized data collection methods, use of harmonized definitions to monitor co-morbidity, symptom, and exacerbation burdens, as well as care and treatment of patients with COPD, using both EHR and PRIO data sources. 18,19 The preponderance of smokers or ex-smokers, overweight or obese patients, and high prevalence of comorbidities in our study, and the almost equal distribution of males and females have been reported by others. [24][25][26][27][28] Our prevalence of nonsmokers (12% in both COPD-RD and APEX-COPD) is in agreement with that reported by Celli and colleagues (13%), 29 but lower than that estimated by the Centers for Disease Control and Prevention (25%).…”
Section: Discussionsupporting
confidence: 81%
“…apexcopd.org/) is the first primary care health system-based COPD registry in the United States. 18,19 It was designed as an observational, primary care initiative which retrospectively and prospectively collects electronic health record (EHR) COPD variables (derived from larger data set-the COPD Optimum Patient Care Research DARTNet Research Database [COPD-RD]). And, unlike other registries, it links these EHR data to patient-reported information/outcomes (PRIO) data and information gathered from COPD patients during primary care visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 OPC also has a well-established track record in COPD research in primary care [41][42][43][44] including the establishment of a COPD patient registry. 45,46 A recent evaluation of a COPD QIP led by OPC demonstrated an overall 20% reduction of COPD exacerbations, compared to 10% in control practices, in the year following implementation. 38 In July 2020, OPC Global, in a collaborative effort with AstraZeneca and the Observational and Pragmatic Research Institute (OPRI), established the COllaboratioN on QUality improvement initiative for achieving Excellence in STandards of COPD care (CONQUEST) program as the first-of-its-kind QIP with data which builds into a collaborative and interventional COPD registry (https://conquest.care/).…”
Section: Background and Aims Of The Conquest Quality Improvement Programmentioning
confidence: 99%
“…There have been a number of well-reported largescale RWD for various clinical care domains, for example, the Clinical Practice Research Datalink (CPRD) which is a primary care database of anonymized medical records [13], European Severe Heterogeneous Asthma Registry, Patient-centred (SHARP) Clinical Research Collaboration [14], UK Severe Asthma Registry (UKSAR) [15], US Advancing the Patient EXperience (APEX) in Chronic Obstructive Pulmonary Disease (COPD) [16] registry amongst others.…”
Section: Introductionmentioning
confidence: 99%